2022
DOI: 10.1093/narcan/zcac027
|View full text |Cite
|
Sign up to set email alerts
|

SFPQ promotes RAS-mutant cancer cell growth by modulating 5′-UTR mediated translational control of CK1α

Abstract: Oncogenic mutations in the RAS family of small GTPases are commonly found in human cancers and they promote tumorigenesis by altering gene expression networks. We previously demonstrated that Casein Kinase 1α (CK1α), a member of the CK1 family of serine/threonine kinases, is post-transcriptionally upregulated by oncogenic RAS signaling. Here, we report that the CK1α mRNA contains an exceptionally long 5′-untranslated region (UTR) harbouring several translational control elements, implicating its involvement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…4A ) [ 26 ]. Other proteins included SFPQ, which modulates 5′‐UTR mediated translational control [ 27 ], and ribosomal proteins (RPL11, RPSA, RPS5, and MRPL1), which can bind the ribosome assembly factor RNA helicases [ 28 , 29 ]. Several mitochondrial proteins (NDUFA9, MT‐CYB, MT‐ATP6, SDHD, and ATP6V0B) were observed in the DTI networks.…”
Section: Resultsmentioning
confidence: 99%
“…4A ) [ 26 ]. Other proteins included SFPQ, which modulates 5′‐UTR mediated translational control [ 27 ], and ribosomal proteins (RPL11, RPSA, RPS5, and MRPL1), which can bind the ribosome assembly factor RNA helicases [ 28 , 29 ]. Several mitochondrial proteins (NDUFA9, MT‐CYB, MT‐ATP6, SDHD, and ATP6V0B) were observed in the DTI networks.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has demonstrated that CK1α expression is regulated by an IRES in the 5‘-UTR of CK1α mRNA. From analysis using HCT-116 cells, SFPQ and PSPC1 were identified as interacting proteins of this IRES, and SFPQ knockdown decreases the CK1α protein abundance, which suggests that SFPQ activates the IRES-dependent translation of CK1α [ 97 ]. SFPQ silencing suppresses in vitro proliferation of HCT-116 cells via KRAS mutation-dependent manner, and exogenous CK1α overexpression rescues this growth defect.…”
Section: Multiple Functions Of Dbhs Family Proteins In Cancer Pathoph...mentioning
confidence: 99%